2020
DOI: 10.1007/978-3-030-50249-2_42
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Online Escape Game for Older Adults: The Implications of Playability Testing Sessions with a Variety of Dutch Players

Abstract: This study evaluated the playability of an online escape game designed using a User-Centred Design (UCD) process for older adult players aged 65 and older. The participants were 30 Dutch older adults who played the game in pairs on tablets over 15 game sessions. The data were collected through surveys, interviews, and observation field notes. The results indicated that, overall, the players enjoyed the game. They enjoyed the collaborative nature of the game and the game challenges the most. They also thought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We adopt a user-centered design approach (Karat, 1996), which emphasizes involving potential users throughout an iterative system design and development process. Several studies have shown great success by using a user-centered design approach in designing digital games for older adults and delivering outcomes that fulfilled their expectations and needs (Doppler et al, 2018;Doroudian et al, 2020;Sauvé & Kaufman, 2019). By involving older adults throughout the whole process, we intended to gather the user requirements of older adults in playing digital games and design digital games that suit their preferences and needs, with a focus on enhancing their social interaction in a distance setting.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We adopt a user-centered design approach (Karat, 1996), which emphasizes involving potential users throughout an iterative system design and development process. Several studies have shown great success by using a user-centered design approach in designing digital games for older adults and delivering outcomes that fulfilled their expectations and needs (Doppler et al, 2018;Doroudian et al, 2020;Sauvé & Kaufman, 2019). By involving older adults throughout the whole process, we intended to gather the user requirements of older adults in playing digital games and design digital games that suit their preferences and needs, with a focus on enhancing their social interaction in a distance setting.…”
Section: Methodsmentioning
confidence: 99%
“…7. Offering customizable fonts or icons can provide a more satisfying player experience for older adults, according to previous studies (Al Mahmud et al, 2012;Doroudian et al, 2020;Mubin et al, 2008) and a review by Rienzo and Cubillos (2020) in playability and player experience in digital games for older adults. Building on this finding, we started the first iteration with a prototype that incorporated a customization feature.…”
Section: Design Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations